DESIGN OF MUL TIBAND FILTERS BASED ON HYBRID POLYNOMIALS - ELDEN , ZEE CHIEN PHENG (2017)
Multiband filters are gaining importance in filter design industry due to the increased demand in multi-bandwidth support and coexistence in a single device. Although many researches had been done, The key challenges can be seen in its sizing, complexity and lack of a comprehensive synthesis method that covers both lumped and distributed element.